IFPRI Malawi monthly maize market report, August 2020 - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
During the month of August, prices fell by 1 percent. The average retail price was MWK 175/kg. This price is 19 percent lower than in August 2019 but 46 percent higher than in August 2018. Since the beginning of August, prices fell in 8 markets, stayed constant in 12, and rose in 6 markets (Table 1). Liwonde market recorded the largest price decline (10 percent) while Lunzu recorded the largest increase (8 percent) closely followed by Mangochi (7 percent).